Effect of calcium hydroxide and chlorhexidine medicaments on the apical seal - Hamidi, Mahmoud-Reza; Mahmoudi, Elham; Moghadamnia, Ali-Akbar; zahedpasha, samir (Iranian Endodontic Journal, 2011)
Introduction: Leakage of the root canal system is an importent consideration when placing an intracanal medicament. The aim of this in vitro study was to compare the effect of calcium hydroxide and 1% chlorhexidine gel as intracanal medicaments on tooth apical seal. Materials and Methods: Seventy extracted, single-rooted maxillary anterior teeth were divided into the three experimental groups (n=20). All root canals were instrumented with step-back technique and divided into three groups. Group 1 had root canal dressing with calcium hydroxide; group 2 had root canal dressing with 1% chlorhexidine gel and group 3, did not receive a dressing. The roots were incubated in 100% humidity at 37°C for 7 days. After removing the dressings, all canals of the experimental groups were obturated using a cold lateral condensation technique. The root surfaces of all specimens were coated with two layers of nail varnish, except for the 2 mm surrounding the apical foramen. Apical sealing ability was assessed by dye leakage method and the specimens were examined under a stereo-microscope. Dye penetrations were measured and analyzed using ANOVA and post-hoc Tukey test. Results: Calcium hydroxide group had the least frequency of apical leakage at 2 mm level (0.46±0.40 mm), whilst chlorhexidine group showed the greatest apical leakage (0.86±0.42 mm). There was statistical difference between group 1 and 2 (P<0.05), but no statistical difference between group 1 and 3, or between groups 2 and 3 (P>0.05). Conclusion: Intracanal calcium hydroxide medicament may decrease apical leakage of gutta-percha root fillings when AH26 sealer is used; chlorhexidine may increase the leakage.